Development of multi-reactive aptamers for Cronobacter spp. using the sequential partitioning method to detect them in powdered infant formula - KIM HYE RI; Kim, Byoung Chan (Elsevier BV, 2023)
Cronobacter spp. are opportunistic foodborne pathogens typically detected in contaminated powdered infant formula (PIF). Thus, the rapid detection and control of Cronobacter spp. are required to prevent outbreaks, necessitating the development of specific aptamers. In this study, we isolated aptamers specific to all seven species of Cronobacter (C. sakazakii, C. malonaticus, C. turicensis, C. muytjensii, C. dublinensis, C. condimenti, and C. universalis) using a newly proposed sequential partitioning method. This method avoids the repeated enrichment steps, reducing the total aptamer selection time compared with the conventional systematic evolu-tion of ligands by the exponential enrichment (SELEX) process. We isolated four aptamers showing high affinity and specificity for all seven species of Cronobacter, with dissociation constants of 3.7-86.6 nM. This represents the first successful isolation of aptamers for multiple targets using the sequential partitioning method. Further, the selected aptamers could effectively detect Cronobacter spp. in contaminated PIF.